Diagnostic and prognostic value of the AST/ALT ratio in patients with sepsis and septic shock - Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Forner, Jan; Dulatahu, Floriana; Brück, Lea Marie; Hoffmann, Ursula; Bertsch, Thomas; Weiß, Christel; Akın, Ibrahim; Behnes, Michael (Scandinavian journal of gastroenterology, 2023)
The study investigates the diagnostic and prognostic value of the aspartate aminotransferase (AST) to alanine aminotransferase (ALT) ratio in patients with sepsis and septic shock. Limited data regarding the prognostic value of the AST/ALT ratio in patients suffering from sepsis or septic shock is available. Consecutive patients with sepsis and septic shock from 2019 to 2021 were included monocentrically. Blood samples were retrieved from day of disease onset (day 1), day 2, 3, 5 and 7. First, the diagnostic value of the AST/ALT ratio was tested for septic shock compared to sepsis. Second, the prognostic value of the AST/ALT ratio was tested for 30-d all-cause mortality. Statistical analyses included univariable t-test, Spearman’s correlation, C-statistics, Kaplan-Meier analyses, as well as multivariable mixed analysis of variance (ANOVA), Cox proportional regression analyses and propensity score matching. A total of 289 patients were included, of which 55% had sepsis and 45% septic shock. The overall rate of all-cause mortality at 30 d was 53%. With an area under the curve (AUC) of 0.651 on day 1 and 0.794 on day 7, the AST/ALT ratio revealed moderate but better diagnostic discrimination of septic shock compared to bilirubin. Furthermore, the AST/ALT ratio was able to discriminate 30-d all-cause mortality (AUC = 0.624; 95% CI 0.559 − 0.689; p = 0.001). Patients with an AST/ALT ratio above the median (>1.8) had higher rates of 30-d all-cause mortality compared to lower values (mortality rate 63 vs. 43%; log-rank p = 0.001), even after multivariable adjustment (HR = 1.703; 95% CI 1.182 − 2.453; p = 0.004) and propensity score matching. The AST/ALT was a reliable diagnostic tool for the diagnosis of septic shock as well as a reliable tool to predict 30-d all-cause mortality in patients suffering from sepsis and septic shock.
Online veröffentlicht: 18. Oktober 2022
Gesehen am 29.07.2024